Influence of Gender Diversity, Institutional Ownership, Environmental Performance, and Audit Committee on Carbon Emission Disclosure: Empirical Study on Energy Sector Companies Listed on the Indonesia Stock Exchange in 2019-2022 - Dwinajayanti, Risky; Wiralestari, Wiralestari; Olimsar, Fredy (International Journal of Multidisciplinary Approach Research and Science, 2024)
This study aims to determine the effect of gender diversity, institutional ownership, environmental performance, and audit committee on carbon emission disclosure empirical study on energy sector companies listed on the Indonesia Stock Exchange in 2019-2022. The population in this study were energy sector companies totaling 74 companies. The sample of this study was selected using purposive sampling method where the sample was selected based on the criteria set by the researcher and got a sample of 93 samples from 30 companies. This study uses secondary data where the data is obtained from the company's annual and sustainability reports obtained from the company's official website and from the official website of the Indonesia Stock Exchange. The analysis method in this study uses multiple linear regression analysis which is processed using the SPSS version 23.0 for windows program. The results of this study show that carbon emission disclosure is influenced by all variables at the same time. Then the environmental performance variable has a significant effect on the disclosure of carbon emissions. Meanwhile, the variables of gender diversity, institutional ownership, and audit committee have no significant effect on the disclosure of carbon emissions.